Funneliformis mosseae Enhances Root Development and Pb Phytostabilization in Robinia pseudoacacia in Pb-Contaminated Soil - Huang, Li; Chen, Deqiang; Zhang, Haoqiang; Song, Yingying; Chen, Hui; Tang, Ming (Frontiers in Microbiology, 2019)
It is possible that arbuscular mycorrhizal fungi play a pivotal role in root development and Pb phytostabilization in plants grown in Pb-contaminated soil. In this study, a pot experiment was conducted over 4 months to evaluate the effects of Funneliformis mosseae strain BGCXJ01A on root characteristics of black locust (Robinia pseudoacacia L.) seedlings in Pb-contaminated soil. Four Pb treatments (0, 90, 900, and 3,000 mg kg–1) were applied to soil in the presence and absence of F. mosseae. Inoculation with F. mosseae prominently improved root length, surface area, volume, and tip number in the plants across all Pb treatments. The F. mosseae inoculation also increased root diameter and fork number, especially under high Pb treatments. The presence of F. mosseae significantly increased the root activity and root tolerance index. However, there was little difference in specific root length between inoculated and non-inoculated plants. The biomass of roots, stems, and leaves all increased following inoculation with F. mosseae. Inoculated plants had greater accumulation and translocation capacities for Pb in the roots and stems, but lower capacities were found in the leaves when compared with those in non-inoculated plants. These results highlight that F. mosseae can alleviate the toxic effects of Pb on root development and can immobilize Pb in the roots and stems of R. pseudoacacia grown in Pb-contaminated soil. This study provides a model system for phytoremediation of Pb-contaminated soil via reciprocal symbiosis between arbuscular mycorrhizal fungi and woody legumes.